2-Amino-5-bromopyridinium 2-phenoxyacetate - Dhanabalan, Nallathambi; Thanigaimani, Kaliyaperumal; Che Khalib, Nuridayanti; Santhanaraj, K. Joseph; Razak, Ibrahim Abdul (International Union of Crystallography, 2016)
The phenoxyacetate anion of the title salt, C5H6BrN2 +C8H7O3 , is essentially planar, with a dihedral angle of 7.6 (5) between the carboxylate group and the benzene ring. In the crystal, the cation and the anion are linked via N—HO hydrogen bonds, forming a helical chain along a 21 screw axis. In the chain, a – stacking interaction between the pyridinium and benzene rings, with a centroid– centroid distance of 3.854 (2) A˚ , and a C—HO interaction are observed. The chains are further linked through another C—HO hydrogen bond, forming a three-dimensional network.